Treatment outcome in T-cell lymphoblastic lymphoma in adults – a population-based study from the Swedish Lymphoma Registry. (July 2014) - Ellin, Fredrik; Jerkeman, Mats; Hagberg, Hans; Relander, Thomas
Abstract Background. T-cell lymphoblastic lymphoma (T-LBL) is a rare neoplasm of precursor lymphoblast origin, for which there is no standard treatment for adults. Results of current treatment strategies in selected populations do exist but are largely unreported for unselected series. Here, we aimed to investigate treatment outcome in a population-based cohort. Material and methods. Patients were identified through the Swedish Lymphoma Registry and data was retrospectively collected for all adult (≥ 18 years) Swedish T-LBL patients diagnosed during 2000–2009. Results. A total of 39 patients with median age 40 years (range 18–78) were identified with females being significantly older than males (median age 66 vs. 37, p = 0.027). The five-year overall survival for all patients was 42%. Female gender was associated with shorter survival also when adjusted for treatment strategy and age [hazard ratio (HR) 4.29; p = 0.002]. Thirty patients received intensive chemotherapy, otherwise used for treatment of acute lymphoblastic leukemia (ALL), which resulted in an overall response rate of 97% and a five-year progression-free survival (PFS) of 49%. In this group only CNS involvement at diagnosis predicted shorter PFS (HR 13.3; p = 0.03). Among patients treated with hyper-CVAD the addition of mediastinal irradiation resulted in prolonged time to progression compared to patients receiving only chemotherapy (p = 0.047). The major reason for treatment failure was relapse and in this series 18-fluoro-deoxyglucose positron emission tomography (PET) did not predict this risk. Conclusion. This population-based study indicates that all fit T-LBL patients should be considered for intensive treatment. Our results also suggest a beneficial effect of mediastinal irradiation in combination with hyper-CVAD treatment. Relapsing patients have a dismal outcome irrespective of salvage treatment.